Pengembangan Buku & Video Kepemimpinan dan Komunikasi Pelatih Sepakbola - Raja Bintang Abrori; Nawan Primasoni (Jurnal Kepelatihan Olahraga, 2022)
This study aims to develop learning media formed book and video of leadership and coach communication in football to build understanding about the importance of leadership and communication in the world of coaching. The research method used is research and development referenced to the burg and gall’s research steps which is simplified by Puslitjaknov team. The subjects of this study were the college student of football coaching who has been passed the Leadership and Coaching Communication. Small group trial was conducted on 12 respondents, large group trial with 40 respondents. The instrument used were questionnaire and evaluation sheet. The obtained results data are quantitative and qualitative descriptive. Qualitative data are analysed using a scale so that it can show the level of product feasibility. The results of the study show that the book and visualization video of leadership and coach communication in football is feasible for learning media. These results were obtained from the material expert’s validation of 96.8% which means good / feasible and media expert’s validation of 88% which means good / decent. In a small group trial, this product received an assessment result of 81.5% which is categorized as good / decent, while in the trial of a large group this product got scored 86.48% which is categorized as good and feasible to use. It can be concluded that this product is good / feasible to use. As suggestions, this book and visualization video can be developed further through comprehensive research.